Styles of Regulators: Evidence from the SEC's Comment Letters† - Do, Truc (Peter) Thuc; Zhang, Huai (Contemporary Accounting Research, 2022)
ABSTRACT We investigate whether individual securities regulators exhibit personal styles in their work, a question of importance to corporate executives and capital market participants. Using the SEC's comment letters as our setting, we find that SEC staff members exhibit unique personal “styles.” We manually collect information on SEC staff members and provide evidence that staff members' personal characteristics influence the SEC's review process. Further analyses reveal that SEC staff members with a CPA qualification are associated with a lower likelihood of future accounting restatements; moreover, similarity between the SEC staff member and the firm's correspondent is associated with lower scrutiny intensity. Overall, our study offers evidence that SEC staff members exhibit individual differences and that their styles shape the SEC's enforcement actions. Our results offer implications for the working of securities regulators.